Languages and Compilers for Parallel Computing - Adve, Vikram (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the 20th International Workshop on Languages and Compilers for Parallel Computing, LCPC 2007, held in Urbana, IL, USA, in October 2007.